The reversible DNA-alkylating activity of duocarmycin and its analogues. - Asai, A (1994)
Intact drugs with spirocyclopropylhexadienone moieties can be regenerated from the covalent DNA adducts induced by antitumor antibiotics duocarmycin (DUM) A, SA and some DUMA analogues in neutral aqueous solution. We detected the reversible nature of DUMs by determination of the antimicrobial activity and cytotoxicity of DUM-DNA adducts. All of the adducts selectively inhibited the growth of a sensitive strain of Bacillus but not that of the wild type strain, a property of parent DUM and its analogues. Most of the DNA adducts were also cytotoxic to HeLa S3. These results suggested that active drugs can be released from their covalent DNA adducts under these biological assay conditions. Regeneration of intact drugs was quantitatively analyzed by HPLC and the amount of free drug released from DNA adducts revealed that the rate and efficiency of this reversal were dependent on structural variables among the drugs. The differences in rates of reversibility were correlated with the biological activity of DUMs. The effect of pH, temperature and salt concentration on the regeneration of drugs from their DNA adducts suggest a catalytic role of double-helical DNA on the reversal pathway.